The influence of oxoG on the electronic properties of ds-DNA. Damage versus mismatch: A theoretical approach. (June 2021) - Karwowski, Boleslaw T.
Graphical abstract: Highlights: Charge transfer is involved in protein cross talking through ds-DNA. dA::dG oxo pair appearing in the genome can lead to a mutation. MutY recognise DNA damage site by an electron charge transfer mode. dA::dG OXO is predisposed to electron attachment and is a better substrate for a MutY than dA:dG. Abstract: The seed of life is concealed in the base sequence in DNA. This macromolecule is continuously exposed to harmful factors which can cause it damage. The stability of genetic information depends on the protein efficiency of repair systems. Glycosylases are the scouts which recognize and remove damaged bases. Their efficiency depends on how rapidly they recognize DNA lesions. One theory states that charge transfer is involved in protein cross talking through ds-DNA. For these reasons a comparative analysis of ds-oligo containing a mismatched base pair dA:::dG and a damaged dA::dG OXO is proposed. Additionally, the electronic properties of the short ds-oligo in the context of non-equilibrated and equilibrated solvent modes were taken into theoretical consideration. All energetic calculations were performed at the M062x/6-31++G** level of theory, while for geometry optimized ONIOM methodology was used. The lowest adiabatic ionization potential was assigned for DNA containing a dA:dG OXO pair. Moreover, the adiabatic electron affinity was assigned at the same level for the mismatched and lesioned ds-oligo. Surprisingly, in the non-equilibrated mode, a significantly higher vertical electro affinity was found for lesioned DNA. The higher VEA in a non-equilibrated solvent state supported faster recognition in the A:G OXO base pair than A:G by MutY glycosylases under electron transfer mechanism.